(untitled) (Revista Contexto & Saúde, 2026)
The objective of this study is to analyse the prevalence of acute toxicity in gynecological cancer patients undergoing brachytherapy at a cancer treatment center in Santa Catarina. This was a descriptive, exploratory cross-sectional study with a quantitative approach. Data were collected from electronic medical records from the oncology referral service. The population comprised patients diagnosed with gynecological cancer who started and completed teletherapy followed by brachytherapy from January to December 2022. The total population consisted of 90 women, and the main toxicity reported was grade 0 radiodermatitis, followed by dysuria and diarrhoea. Other toxicities were observed in the gastrointestinal and genitourinary systems, such as nausea, insomnia, decreased appetite, grade I radiodermatitis, fatigue, vaginal discharge, loose stools, and lower abdominal pain. Identifying the toxicity profile of women undergoing radiotherapy assists the multidisciplinary team in patient care and management.